Penerapan Strategi Pemasaran Digital Bisnis Kuliner Rumahan Bagi Jemaat GKP Klasis Jakarta-Banten - Carolina F. Sembiring; Nenny Anggraini; Arya Gina Tarigan; Maria Yulan Christina; Virginia Poppi Panjaitan; Flora Ferdinanda Imoliana (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2025)
The bakery business, particularly dry cakes, has rapidly grown as part of the promising food and beverage industry, especially during significant religious events. To support this, the Economic Development Commission of the Church of the Christian Pasundan Synod of Jakarta and Banten is working to encourage the congregation’s economy and improve family income through the empowerment of small businesses (UMKM) in the dry cake sector, led by one of the congregation members, Mrs. Wenny Widiawati, with her business "Kuenya Afra." However, challenges include how to market the dry cakes both offline and digitally, calculate the cost of goods sold (HPP), and identify potential business risks for home-based businesses. This Community Service program aims to enhance the understanding of the importance of implementing the right marketing strategies, calculating HPP, managing business risks, and creating business accounts on social media. The conclusion from this community service activity is that the partner, especially the owner of "Kuenya Afra" and the church congregation, greatly benefited from understanding the importance of implementing digital marketing strategies to expand their customer base. Through this socialization and mentoring program, it is expected to increase entrepreneurial spirit and sales beyond the limited congregation environment. The activity was held onsite at the Gereja Kristen Pasundan Ebenhaezer Church in Cawang, Jakarta.